Pengaruh Nilai Personal Terhadap Modal Sosial Pedagang Di Kota Bukittinggi - Yulhendri Yulhendri; Nur Fadhila Arivino (Jurnal Ecogen, 2023)
Personal values are one of the factors forming social capital. This studi examined the imoact that individual values have on the social capital that merchants in Bukittinggi City prossess. The population in this research are traders in Bukittinggi City. This research uses descriptive statistical methods, namely data analysis to obtain the distribution of respondents' answers through mean size, standard deviation and inferential statistical analysis through Structural Equition Model (SEM) with Partial Least Square (SEM-PLS) to analyze the influence between variables. The software used for SEM PLS analysis is the SmartPLS-4 program. The results of this research state that Personal Values directly have a positive and significant effect on increasing good Social Capital among traders in Bukittinggi City.